IMPACTS OF FREEZING TEMPERATURES ON CROP PRODUCTION IN CANADA - BROWN, D. M.; BLACKBURN, W. J. (Canadian Journal of Plant Science, 1987)
Subzero temperatures are the most widespread hazard to crop production in Canada. This hazard ranges from temperature occurrences near 0 °C in spring and fall that damage many annual crops and some perennials to the winter occurrences of −30 °C and lower that damage or kill vegetative and/or reproductive tissues of some perennial species. Terminology, types of freeze damage, and the freeze risk are reviewed and discussed here along with some examples of the occurrence and adverse impact of freezing temperatures for the range of annual, winter annual and perennial crops grown in Canada. Spring grain losses from freeze damage occur about once every 3–4 yr in Saskatchewan, less frequently in Alberta (except the Peace River region), Manitoba and the northern clay belts in Ontario and Quebec, and seldom in the remainder of eastern Canada. Frequency of canola losses on the Prairies has been similar to cereals over the past 10–12 yr. The availability of short-season corn and soybean cultivars has expanded the production of these crops to areas with fewer than 2300 heat units over the last 20 yr. This has resulted in more frequent losses of these crops from fall freezes. Major losses of seed-corn occurred in southwestern Ontario on three occasions from 1965 to 1974, but very little freeze damage has occurred since 1974. Losses of vegetable crops from freezing occur less frequently than other crops because of the well-established cultural practices developed over the years that avoid or protect from frost. The high value per unit area of most vegetables makes freeze protection more affordable when needed. Forages and winter annuals are killed more frequently in central and eastern Canada by smothering and desiccation from formation of ice sheets than from low winter temperatures. Injury to young shoots and leaf buds of these crops occurs periodically from spring freezes. Losses of fruit trees occur periodically and apparently occurred more frequently 20–35 yr ago in British Columbia, whereas losses have been more severe ...